Psychological flourishing of postgraduate students in Klang Valley, Malaysia - Ch’ng, Brendan; Mariani Md Nor,; Loh, Sau Cheong (Penerbit Universiti Kebangsaan Malaysia, 2022)
Across the world including Malaysia, the rate of mental health issues has become increasingly concerning especially among young adults. However, much is still unknown about the psychological flourishing of postgraduate students despite the steady increase in student enrolments into postgraduate programmes as Malaysia anticipates the emergence of a skilled talent pool to advance the nation’s economic growth. Thus, this quantitative study explored the psychological flourishing of Malaysian postgraduate students in Klang Valley by examining whether there are significant differences based on their sociodemographic characteristics. A total of 240 postgraduate students participated in this study and completed a set of questionnaires online that measured their psychological flourishing and demographic characteristics. The results showed that there were significant differences in the psychological flourishing of postgraduate students based on their age group and field of study. However, this study did not find any significant differences in postgraduate students’ level of psychological flourishing based on their gender, ethnicity, level of postgraduate programme, the structure of programme, mode of programme, and year of programme. The findings of this study had several practical implications for postgraduate students, faculty members, and on-campus counsellors. Finally, the limitations of this study and recommendations for future studies are also addressed.